AN ECRANISATION STUDY OF NOVEL THE KITE RUNNER AND ITS FILM ADAPTATION - Khissoga, Rahajeng Hauwwa (Universitas Muhammadiyah Jember, 2023)
This research studied about Ecranisation Study of Novel into Film The Kite Runner. The purpose of this study is to ascertain how the novel The Kite Runner was reduced, added, and modified for the cinema adaptation. The reduction, addition, and modification in the ecranisation study were analyzed using descriptive qualitative methodology and the theory of Eneste's Ecranisation. The data collections of this research are intrinsic elements contained in both novel The Kite Runner and the film The Kite Runner. The researcher employed note-taking as a tool for data collection in order to find out the reduction, addition, and modification of novel into film. The plot, the characters, the point of view, and some of the events and depictions in this study have all undergone some reduction, and alteration. However, the researcher could not find any addition in the process of the adaptating novel The Kite Runner into Film The Kite Runner.